Interrupting the Legal Person - Sarat, Austin (Studies in Law, Politics, and Society Ser., 2022)
This special issue is part one of a two-part edited collection on interrupting the legal person, and what this means. The chapters in this volume interrogate the role of the person and personhood in different contexts, jurisdictions, and legal traditions.